Access to and quality of early childhood education and care policies in Europe - Akvile Motiejunaite (IUL Research)
European policy is moving from emphasising the need for childcare towards establishing every child’s right to quality early childhood education and care (ECEC). In practice, access to ECEC remains the main priority and the only policy aspect where a specific target has been agreed. This paper argues for the need for clearer guidance to promote quality ECEC. It proposes a composite indicator to monitor ECEC system integration based on: integrated governance, bachelor’s degree for staff, educational guidance, and place guarantee. The analysis reveals a large variation regarding the degree of ECEC system integration in the European Union countries. During the last ten years, half of the EU Member States expanded children’s legal rights to access ECEC. Yet, significant reforms improving ECEC system integration were scarce.